High Resistance of Potato to Early Blight Is Achieved by Expression of the Pro-SmAMP1 Gene for Hevein-Like Antimicrobial Peptides from Common Chickweed (Stellaria media) - Denis V. Beliaev; Natalia O. Yuorieva; Dmitry V. Tereshonok; Ilina I. Tashlieva; Marina K. Derevyagina; Alexei A. Meleshin; Eugene A. Rogozhin; Sergey A. Kozlov (Plants, 2021)
In the common chickweed Stellaria media, two antimicrobial peptides (AMPs), SmAMP1.1a and SmAMP1.2a, have been shown to be proteolytically released as products of the expression of a single gene, proSmAMP1. In this study, the gene proSmAMP1 was introduced into two potato varieties, Zhukovsky ranny and Udacha. These early-maturing varieties were shown to be susceptible to early blight caused by Alternaria spp. Most transgenic lines of either variety having strong expression of the target gene demonstrated high levels of resistance to Alternaria spp. during three years of cultivation, but did not otherwise differ from the initial varieties. Disease severity index (DSI) was introduced as a complex measure of plant susceptibility to early blight, taking into account the diameter of lesions caused by the Alternaria spp., the fungus sporulation intensity and its incubation period duration. Across all transgenic lines, the DSI inversely correlated both with the target gene expression and the copy number in the plant genome. Our results are promising for improving the resistance of potato and other crops to early blight by expression of AMPs from wild plants.